Mechanism of SET8 Activates the Nrf2-KEAP1-ARE Signaling Pathway to Promote the Recovery of Motor Function after Spinal Cord Injury - Xin Li; Yan Qian; Wanling Shen; Shiying Zhang; Hui Han; Yu Zhang; Shuangmei Liu; Shaokun Lv; Xiuying Zhang (Mediators of Inflammation)
Background. Spinal cord injury (SCI) is a common injury of the central nervous system (CNS), and astrocytes are relatively abundant glial cells in the CNS that impairs the recovery of motor function after SCI. It was confirmed that the oxidative stress of mitochondria leads to the accumulation of reactive oxygen species (ROS) in cells, which plays a key role in the motor function of astrocytes. However, the mechanism by which oxidative stress affects astrocyte motility after SCI is still unexplained. Therefore, this study investigated the influence of SET8-regulated oxidative stress on astrocyte autophagy levels after SCI in rats and the potential mechanisms of action. Methods. We used real-time quantitative PCR, western blotting, and immunohistochemical staining to analyze SET8, Keap1, and Nrf2 expression at the cellular level and in SCI tissues. ChIP to detect H4K20me1 enrichment in the Keap1 promoter region under OE-SET8 (overexpression of SET8) conditions. Western blotting was used to assess the expression of signature proteins of astrocytes, proteins associated with autophagy, proteins associated with glial scar formation, reactive oxygen species (ROS) levels in cells using DHE staining, and astrocyte number, morphological alterations, and induction of glial scar formation processes using immunofluorescence. In addition, the survival rate of neurons after SCI in rats was examined by using NiSSl staining. Results. OE-SET8 upregulates the enrichment of H4K20me1 in Keap1, inhibits Keap1 expression, activates the Nrf2-ARE signaling pathway to suppress ROS accumulation, inhibits oxidative stress-induced autophagy and glial scar formation in astrocytes, and leads to reduced neuronal loss, which promoted the recovery and improvement of motor function after SCI in rats. Conclusion. Overexpression of SET8 alleviated oxidative stress by regulating Keap1/Nrf2/ARE, inhibited astrocyte autophagy levels, and reduced glial scar formation as well as neuronal loss, thereby promoting improved recovery of motor function after SCI. Thus, the SET8/H4K20me1 regulatory function may be a promising cellular therapeutic intervention point after SCI.